The Effect of Brand Image and Promotion on Gluten Rice Sobi Milk Purchase Decisions in Bandar Lampung - Fashiyamu F, Ajeng; Ambarwati, Dwi Asri Siti (Journal of Business Management and Economic Development, 2025)
The culinary sector is one of the most thriving industries in Indonesia, leading to intense competition among businesses in developing effective strategies. This study examines the influence of brand image and promotions on purchase decisions at Ketan Susu Sobi, a small business in Bandar Lampung. Brand image and promotions are critical components in marketing, particularly for small businesses (UMKM) striving to thrive in a competitive market. Data was collected through a questionnaire using a quantitative approach and survey method. Multiple linear regression analysis was employed to assess the impact of the independent variables, brand image and promotion, on the dependent variable, purchasing decisions. The findings reveal that brand image has a significant positive effect on purchase decisions, with a significance value of 0.000, which is less than 0.05. Consumers are more likely to choose products with a strong brand image because they instill trust and offer perceived added value. Similarly, promotions also significantly affect purchasing decisions, with a significance value of 0.000, indicating that most respondents are motivated to buy Ketan Susu Sobi after seeing promotions on social media. The study provides valuable insights for Ketan Susu Sobi to enhance its brand image through product innovation and maintain its reputation while developing creative promotional strategies to engage a broader audience.